EVALUATING SERVICESCAPE OF THE PREMIERE CINEPLEX 21 GROUP IN MANADO TOWN SQUARE 3 USING IMPORTANCE AND PERFORMANCE ANALYSIS - Sumampouw, George Gary; Pangemanan, Sifrid .; Rumokoy, Farlane S (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Many company provide greater leisure service settings or arrange another leisure service settings to attract consumers and also make profit, movie theater is one of a kind of leisure service setting. Appearanced of The Premiere movie theaters in Manado become a phenomena although this kind of movie theater already introduced by other company that provide premium movie theater. This research aims to evaluate the servicescape of The Premiere Cineplex 21 Group in Manado Town Square 3. Type of this research is descriptive with quantitative approach and IPA used as the measurement tool. The sample size of this research is 100 respondents who already experience watching movie in The Premiere Cineplex 21 Group in Manado Town Square 3. Convenience sampling was used to collecting data through online questionnaire.The result, the servicescape of The Premiere Cineplex 21 Group in Manado Town Square 3 shows, the cleanliness inside the studio attribute located in Quadrant 2. On the other hand, electric seats inside the studio attribute placed in Quadrant 3 on IPA chart about servicescape of The Premiere Cineplex 21 Group in Manado Town Square 3. The Premiere needs to improve all of them in order to keep the market share they have already created otherwise to keep satisfying their customers, and creating further repatronage intention. Keywords: importance and performance analysis, servicescape, leisure service setting, the premiere, cineplex 21 group.